THE ROLE OF MINDFULNESS PRACTICES IN FORMING EMOTIONAL COMPETENCE OF HOTEL AND RESTAURANT BUSINESS STAFF (Development Service Industry Management, 2025)
The article is devoted to the study of the role of mindfulness practices in the formation of emotional competence of hotel and restaurant staff. The work reveals the essence of the concept of mindfulness, its psychological and organizational foundations, as well as the importance of mindfulness for effective management of emotions, stress and professional communications of hospitality employees. Particular attention is paid to the analysis of modern approaches and methods of implementing mindfulness programs in the professional environment, as well as their impact on improving the quality of service, developing corporate culture and strengthening customer loyalty.The study examines successful cases of mindfulness programs in international hotel chains, using the example of «Marriott», where mindfulness is used as a tool for developing emotional intelligence, team interaction and stress resistance. It is noted that mindful practices contribute to improving the psychological climate in the team, reducing burnout and forming a positive brand image focused on caring for employees and guests.Based on the analysis of theoretical and practical data, recommendations are proposed for the management of hotel and restaurant enterprises regarding the integration of mindfulness approaches into HR-strategy and personnel training systems. These recommendations are aimed at increasing emotional resilience, developing empathy, and strengthening the competitiveness of enterprises in a dynamic service market.Finally, the need for a comprehensive approach to the implementation of mindfulness programs as an element of sustainable development of the hospitality industry is emphasized. Promising areas of further research are identified, including assessing the effectiveness of mindfulness programs and adapting mindfulness practices to the cultural characteristics of an international audience.
Keywords: mindfulness; meditation; emotional competence; hotel and restaurant business; personnel management; service; emotional intelligence; stress resistance; corporate culture; hospitality